2002
DOI: 10.1074/jbc.m209427200
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 1 Regulates Connexin-43 Gap Junction Assembly

Abstract: Phosphorylation of members of the connexin family of gap junction proteins has been correlated with gap junction assembly, but the mechanisms involved remain unclear. We have examined the role of casein kinase 1 (CK1) in connexin-43 (Cx43) gap junction assembly. Cellular co-immunoprecipitation experiments and in vitro CK1 phosphorylation reactions indicate that CK1 interacted with and phosphorylated Cx43, initially on serine(s) 325, 328, or 330.32 P i -Metabolically labeled cells treated with CKI-7, a specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
169
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(176 citation statements)
references
References 45 publications
5
169
2
Order By: Relevance
“…4). In addition, previous work from our lab has shown that Casein Kinase 1 is important for plaque formation, as inhibition of CK1 led to a decrease in gap junction plaques and an increase in hemichannels in the plasma membrane (Cooper & Lampe, 2002). Taken together, these data are consistent with the idea that phosphorylation on some combination of S325/328/330 by CK1 results in a conformational change resulting in the P2 isoform and inclusion in a gap junction plaque.…”
Section: Inclusion In the Gap Junction Plaque And Formation Of P2supporting
confidence: 88%
See 1 more Smart Citation
“…4). In addition, previous work from our lab has shown that Casein Kinase 1 is important for plaque formation, as inhibition of CK1 led to a decrease in gap junction plaques and an increase in hemichannels in the plasma membrane (Cooper & Lampe, 2002). Taken together, these data are consistent with the idea that phosphorylation on some combination of S325/328/330 by CK1 results in a conformational change resulting in the P2 isoform and inclusion in a gap junction plaque.…”
Section: Inclusion In the Gap Junction Plaque And Formation Of P2supporting
confidence: 88%
“…Consistent with Musil and Goodenough (1991), the P2 isoform was insoluble after extraction of cells with Triton X-100 as indicated in the middle lane (Ab: Total, Prep: Tx Ins) of Fig 1A. When that same lane is simultaneously probed with an antibody (pS325) that is specific for Cx43 when it is phosphorylated at S325, S328 and/or S330, we found that only the P2 isoform was present (third lane, Ab:pS325, Prep:Tx Ins). We had previously shown that this phosphospecific antibody labeled the intercalated disk region of cardiomyocytes (Lampe et al, 2006) and that S325/328/330 phosphorylation was important in gap junction assembly (Cooper & Lampe, 2002). In Fig.…”
Section: Formation Of the P2 Isoformmentioning
confidence: 83%
“…As illustrated in Figure 4c, after 6-8 h of incubation with IC261 (see also Materials and methods; Cooper and Lampe (2002) and Li et al (2004)), the signal intensity of nm23 phosphorylation decreased by 65% (quantified by imaging scan analyses; data not shown). To confirm any effects of inhibition of CKI on nm23 phosphorylation in cells and to avoid any misinterpretation relating to the relatively high levels of IC261 used (see below), here we also treated the MDA-MB-H1-177 cells with the two additional CKI inhibitors indicated above: D4476 and CKI-7 (Figure 4d).…”
Section: Resultsmentioning
confidence: 92%
“…In these assays, IC261 was used at a concentration of 50 mM, CKI-7 at 400 mM, and D4476 at 25 mM, according to the concentrations reported in the literature (Cooper and Lampe, 2002;Izeradjene et al, 2004;Li et al, 2004;Rena et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, our results with the p38 MAPK inhibitor SB202190 indicate that the MAPK pathway is responsible, in part, for the inhibitory effects of S. aureus on functional GJC in astrocytes. However, the participation of other kinases that have been shown to interact with Cx43, such as PKC (Martinez et al, 2002;Reynhout et al, 1992), casein kinase 1 (Cooper and Lampe, 2002), PKA (Burghardt et al, 1995;TenBroek et al, 2001), and c-Src Sorgen et al, 2004) cannot be excluded in modulating the S. aureus-induced decrease in Cx43 expression, and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%